Weight cycling and risk of clinical adverse events in patients with heart failure with preserved ejection fraction: a post-hoc analysis of TOPCAT - Tan, Yi; Guo, Hang; Zhang, Ning; Zheng, Keyang; Liu, Guifang (Frontiers in Endocrinology, 2023)
Background: Previous studies hardly evaluated the association of variability of BMI or waist circumference with clinical adverse events and investigated whether weight cycling had effect on the prognosis of patients with HFpEF (heart failure with preserved ejection fraction). Methods: This study was a post-hoc analysis of TOPCAT. Three outcomes were evaluated among primary endpoint, CVD death and heart failure hospitalization. KM curves were used to describe the cumulative risk of outcome and were tested using log-rank test. Cox proportional hazards regression models were used to calculate hazard ratios (HRs) and 95% CIs for outcomes. We also performed a subgroup analysis and several subgroups were compared. Results: A total of 3146 patients were included. In the Kaplan-Meier curves, the CV of both BMI and waist circumference were grouped according to quartiles, with the Q4 group having the highest cumulative risk. (Log-rank P < 0.001) In the coefficient of BMI variation and the outcomes, the HRs for group Q4 of coefficient of variation of BMI were 2.35[95%CI,1.82, 3.03]) for the primary endpoint, 2.40[95%CI,1.69, 3.40]) for death and 2.33[95%CI,1.68, 3.22]) for HF hospitalization in Model 3(fully adjusted model) compared with group Q1. In the coefficient of waist circumference variation and the outcomes, Group Q4 had increased hazard of the primary endpoint (HR,2.39[95%CI,1.84, 3.12]), CVD death (HR,3.29[95%CI,2.28, 4.77]) and HF hospitalization (HR,1.98[95%CI,1.43, 2.75]) in Model 3(fully adjusted model) compared with group Q1. In the subgroup analysis, there was a significant interaction in the diabetes mellitus subgroup (P for interaction=0.0234). Conclusion: Weight cycling had a negative effect on the prognosis of patients with HFpEF. The presence of comorbid diabetes weakened the relationship between waist circumference variability and clinical adverse events.